A framework for successful network alliances for SMEs in China. (1st January 2014) - Rhodes, Jo; Lok, Peter; Cheng, Vincent
This study adopts a qualitative approach to develop an effective network alliance framework for SMEs in China. Six firms with extensive network partners from different industries were selected. The data were triangulated with the support of Nvivo analysis. The result showed that relationship management (inclusive of government relations) and knowledge-sharing management had the highest impact on effective network alliances of SMEs in China.